Motivation and Instructional Preference of EFL Students at Tertiary Level - Dwi Ratnasari (Universitas Jambi, Magister Program of English Education Department, 2019)
The aims of the study to find out the relationship between students’ motivation and instructional preference. The main components of motivation that underlay the students to learn English, and the students’ most preferred instruction, is beneficial to contribute to teachers’ understanding of the need to consider students’ preferences when planning the teaching-learning activities and to choose the instructional methods to use in teaching. A mixed-method design used in this study by combining quantitative and qualitative data to analyze. Descriptive statistics and interview analysis were used. The participants of this study were 323 students at a private university in Palembang, Indonesia. An 82-item questionnaire assessing motivation and instructional preference and semi-structured interview were used. The questionnaire consisted of 50 items measuring motivation and 32 items measuring instructional preference. The result showed that there was a positive and significant relationship between motivation and instructional preference. It means that students who had a higher level of motivation would have more instructional preferences than those who had a lower level of motivation. The result of the study indicated that the primary motivational components underlying the students to learn English were instrumental orientation, intrinsic orientation, and integrative orientation, and the students’ most preferred instruction was mastery learning. This study implies that teachers should be aware of diversifying the instructional methods used in their classes. They should take into account the students’ characteristics when planning and implementing educational processes.